Postnatal Clubs: Implementation Of A Differentiated And Integrated Model Of Care For Mothers Living With Hiv And Their HIV-Exposed Uninfected Babies - Nelson, Aurelie (Department of Public Health and Family Medicine, 2024)
Background Despite the reduction in the HIV mother-to-child transmission (MTCT) rate in South Africa, there are ongoing concerns in the breastfeeding period, linked to poor retention in care. To improve this retention, Post Natal Clubs (PNC) were created as an integrated, differentiated model of care providing psychosocial support and comprehensive care for the mother-infant pairs (MIP). We describe the implementation of PNC and examine its health outcomes in a peri-urban primary health care setting in Cape Town, South Africa. Methods In this cohort study, conducted between June 2016 and December 2019, MIPs were recruited into PNC between 6 weeks and 6 months of age and followed-up until 18 months of age. PNC MIPs were compared to a historical control group from the same setting. Outcomes included maternal Viral Load (VL), HIV testing at 9 and 18 months of age, and other maternal and child health outcomes. Results During the implementation of PNC study period, n=484 MIP were recruited with 84% overall attendance, 95% overall viral load suppression, and 98% overall uptake of HIV infant testing. Compared to historical controls, the PNC infant rapid test completion was 1.6 times higher (95% CI: 1.4-1.9) at 9 months and 2.0 times higher at 18 months (95% CI: 1.6-2.6). Through 12 months and between 12-18 months, maternal VL completion was higher in the PNC group compared to the historical control by 1.5 times (95% CI: 1.3-1.6) and 2.6 times (95% CI: 2.1- 3.2), respectively, with similar maternal VL suppression. Of 105 infants attending the 12 months visit, 99% were fully vaccinated by one year. Conclusion MIP in the PNC showed better PMTCT outcomes than historical controls with high levels of retention in care. Other outcomes such as immunisation results suggest that integration of services, such as in the PNC, is feasible and beneficial for MIPs.